Balance-of-payments-constrained growth model: Empirical evidence from Malaysia - Tuck, Cheong Tang (Universiti Utara Malaysia, 2005)
Applying cointegration approach, the present study aims to examine the validity of the Harrod Thirlwall balance-of-payments-constrained growth model in Malaysia. The results show that real income and real exports are not cointegrated during the period 1960-2000. This reveals that the Harrod- Thirlwall balance-of-payments-constrained growth hypothesis has not been supported in Malaysia.